Race, Space, and Surveillance: Understanding the Relationship between Criminal Justice Contact and Institutional Involvement. (13th March 2018) - Remster, Brianna; Kramer, Rory
Ethnographies of young men of color offer competing theories regarding how individuals react to criminal justice contact. System avoidance theory suggests that black and Latino men in segregated neighborhoods avoid formal institutions because of fear of surveillance, while Rios contends that they frame their criminal justice contact as a racial injustice and become activists. Using data from the National Longitudinal Survey of Adolescent to Adult Health, this study tests these hypotheses. Findings indicate that system avoidance is not specific to men of color, as the original theory posits; criminal justice contact is associated with avoidance for all men in the sample. In contrast, active engagement is partially racialized; men of color with criminal justice contact are more likely to volunteer than white men, but low-level contact is associated with activism for all men. Furthermore, there is little evidence that reactions to criminal justice contact vary by place.